2007
DOI: 10.1161/circulationaha.106.183216
|View full text |Cite
|
Sign up to set email alerts
|

Noninherited Risk Factors and Congenital Cardiovascular Defects: Current Knowledge

Abstract: Abstract-Prevention of congenital cardiovascular defects has been hampered by a lack of information about modifiable risk factors for abnormalities in cardiac development. Over the past decade, there have been major breakthroughs in the understanding of inherited causes of congenital heart disease, including the identification of specific genetic abnormalities for some types of malformations. Although relatively less information has been available on noninherited modifiable factors that may have an adverse eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
353
1
25

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 711 publications
(387 citation statements)
references
References 221 publications
(190 reference statements)
8
353
1
25
Order By: Relevance
“…Smoking, alcohol and drug use, poor maternal diet, obesity, and chronic conditions such as diabetes and hypertension are all more common in depressed patients and are potential risk factors for congenital cardiac anomalies. 34 In addition, depressed, anxious women utilize more health care resources, including ultrasounds, amniocentesis and infant echocardiograms than their healthy counterparts. 35,36 Hence, there is a higher chance of detecting an infant with a cardiac malformation that might have gone clinically undetected in other women, particularly milder defects such as muscular VSDs which often close during early childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking, alcohol and drug use, poor maternal diet, obesity, and chronic conditions such as diabetes and hypertension are all more common in depressed patients and are potential risk factors for congenital cardiac anomalies. 34 In addition, depressed, anxious women utilize more health care resources, including ultrasounds, amniocentesis and infant echocardiograms than their healthy counterparts. 35,36 Hence, there is a higher chance of detecting an infant with a cardiac malformation that might have gone clinically undetected in other women, particularly milder defects such as muscular VSDs which often close during early childhood.…”
Section: Discussionmentioning
confidence: 99%
“…As genetic testing technologies have evolved to offer higher resolutions and greater diagnostic yields than those provided by conventional chromosomal analyses, copy number variants (CNVs) have emerged as important causes of both syndromic and non-syndromic CHDs 9 . Moreover, an increasing recognition of contributing environmental 10,11 and epigenetic 12,13 factors has revealed a previously unanticipated breadth to CHD etiology. Families with Mendelian inheritance have been useful for identifying monogenic causes, although mutations in identified genes have been infrequently detected in unrelated patient cohorts 44 .…”
Section: Genetics and Recurrencementioning
confidence: 99%
“…Furthermore, systems biology approaches designed to assess functional convergence of causative CHD genes and associated transcriptional responders (genes with altered cardiac expression) have suggested that multiple CHD risk factors are more likely to act on different components of a common functional network than to directly converge on a common genetic or molecular target 6,7 . These findings, coupled with an ever-expanding list of CHD-associated gene mutations 8 , chromosomal abnormalities 9 , environmental causes 10,11 , and epigenetic insults 12,13 hint at a significant complexity to both normal heart development and CHD pathogenesis. In the following section, we describe current understanding of the major embryologic events that shape the developing heart.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of chicken and mouse embryos to exogenous homocysteine also resulted in septal defects [7]. Folate supplementation has been implicated in specifically reducing conotruncal anomalies and VSDs [33]. Consequently, the carriers with genetically increased CBS expression would benefit from the protection due to the low homocysteine levels maintained by CBS in certain cells during the critical heart development stages.…”
Section: Discussionmentioning
confidence: 99%